Impacts of grazing on ground cover, soil physical properties and soil loss via surface erosion: A novel geospatial modelling approach. (1st June 2021) - Donovan, Mitchell; Monaghan, Ross
Abstract: Agricultural expansion and overgrazing are globally recognized as key contributors to accelerated soil degradation and surface erosion, with direct consequences for land productivity, and environmental health. Measured impacts of livestock grazing on soil physical properties and ground cover are absent in soil loss models (e.g., Revised Universal Soil Loss Equation, RUSLE) despite significant impacts to surface erosion. We developed a novel model that captures changes to ground cover and soil properties (permeability and structure) as a function of grazing intensity (density, duration, history, and stock type), as well as soil clay and water contents. The model outputs were integrated within RUSLE to calculate a treaded soil erodibility (Ktr ) and grazed cover factors (Cgr ) at seasonal timescales (3-month windows) to account for variability in soil moisture content, grazing practices, vegetation growth and senescence, and rainfall. Grazed pastures and winter-forage paddocks exhibit distinct changes in soil erodibility and soil losses, which are most pronounced for wet soils when plant cover is reduced/minimal. On average, typical pasture grazing pressures increase soil erodibility by 6% (range = 1–90%), compared to 60% (18–310%) for intensive winter forage paddocks. Further, negligible ground cover following forage crop grazing increases surface erosion by a factor of 10 ( ± 1 3 ) relative to grazed pastures, which exhibit soil losses (μ = 83 t km −2 yr −1 ; range = 11.6 to 246) comparable to natural uncropped catchments (100–200 t km −2 yr −1 ). Exacerbated soil losses from winter forage-crop paddocks ( μ  = 1, 100 t km −2 yr −1 ) arose from significant degradation of soil physical properties and exposing soils directly to rainfall and runoff. We conclude that proactive decisions to reduce treading damage and avoid high-density grazing will far exceed reactive practices seeking to trap sediments lost from grazed lands. Highlights: Pastoral grazing increased soil erodibility by 6% and average soil losses by 87%. Modelled soil losses for grazed pastures were 83 t km −2 yr −1 (range: 11 to 246). Forage-crop grazing increased soil loss annually by 1200% relative to pastures. Modelling livestock treading and grazing improves RUSLE model results. Proactively mitigating grazing impacts exceeds reactive sediment traps.